Odpowiedź:
A)
[tex] \frac{2x + 3}{5} = \frac{2 - x}{3} - x[/tex]
3(2x+3)=5(2-x)-15x
6x+9=10-5x-15x
6x+9=10-20x
6x+20x=10-9
26x=1 /:26
[tex]x = \frac{1}{26} [/tex]
B)
[tex] \frac{x - + 1}{2} - \frac{x - 1}{3} = \frac{1}{4} [/tex]
6(x+1)-4(x-1)=3
6x+6-4x+4=3
2x+10=3
2x=3-10
2x=-7 /:2
[tex]x = - \frac {7}{2} [/tex]
C)
[tex] \frac{4x + 7}{2} - \frac{5x - 1}{6} = x + 5[/tex]
3(4x+7)-(5x-1)=6x+30
12x+21-5x+1=6x+30
7x+22=6x+30
7x-6x=30-22
x=8
D)
[tex] \frac{x - 5}{4} - \frac{2x + 1}{8} = \frac{1}{2} \times (2 - x) \div 2| [/tex]
[tex] \frac{x - 5}{4} - \frac{2x + 1}{8} = 1 - \frac{1}{2} x[/tex]
2(x-5)-(2x+1)=8-4x
2x-10-2x-1=8-4x
-11=8-4x
4x=8+11
4x=19 /:4
[tex]x = \frac{19}{4} [/tex]